Lieder on record 1898 - 2012 - Schubert, Franz 1797-1828 (EMI Records, 2012)
"With their tales of lovelorn young men, drinking, fishing and pathless wandering, the lieder lie at the heart of Schubert's aesthetic, born of their own time yet always speaking to us afresh. This survey includes 213 lieder in recordings by 91 singers made over more than a century. All of Schubert's most famous songs are here, often in multiple performances, allowing the listener to get to the heart of the art of the song, and the singer. The baritone Thomas Hampson further explores this art in a specially commissioned documentary. CD16 contains texts and translations, the booklet includes an essay by Richard Stokes." - Container